Optimal low-carbon governance model of livestreaming supply chain based on multiple scenarios - Peng, Liangjun; Lu, Gang; Liu, Mingwu; Liu, Yawei; Zou, Zichen (Frontiers in Environmental Science, 2022)
Climate change has posed a significant threat to global human society. Shopping on the live streaming platforms, especially since the outbreak of COVID-19, have become vastly popular and have demonstrated unparalleled growth around the world, which has caused a lot of carbon emissions to the live streaming supply chain. Currently, optimization models for low-carbon governance of the live streaming supply chain are relatively lacking. Designed to address the issue of carbon emission reduction in the live streaming supply chain, this paper proposes three low-carbon governance decision-making models based on environmental costs and operating costs to compare which governance model is optimal. The best suitable decision result for the policymaker and the supply chain is both cost-effective and environmentally successful under the model considering carbon tax and carbon trade. The results show that (1) governance only by the carbon tax and collaborative operation will decrease the total cost of the live streaming supply chain but increase the environmental cost. (2) Governance only through carbon trading and collaborative operation will increase the total cost of the live streaming supply chain, while the environmental cost will not change. (3) Under governance that combines carbon tax and carbon trading, collaborative operations can effectively reduce both the total cost and the environmental cost of the live streaming supply chain. These results will provide a useful reference for the formulation of a low-carbon policy for the live streaming supply chain.